O Enfrentamento da jurisprudência defensiva recursal pelo código de processo civil à luz do princípio da primazia da resolução do mérito - COSTA, Sarah Maia (2022)
The present work aims to investigate how changes brought about by the Civil Procedure Code that face the positioning of defensive jurisprudence in an appeal scope. In this sense, the work will address the theme in three chapters, the first being dedicated to the exposure of procedural principles that directly privilege the analysis of appeal merit by the judge, such as procedural good faith, efficiency, instrumentality of forms and primacy of resolution merit. In the second chapter, the relationship between procedural formalism and the fundamental right of access to justice will be explored. Finally, in the third chapter, the main changes brought about by the CPC / 2015 will be addressed in appeal, through the provision of general sanitation clauses, in order to guarantee the overcoming of procedural filigree created by defensive jurisprudence. The method used in the research was deductive-argumentative, through the analysis of provisions of Law 13.105 / 2015 (Code of Civil Procedure) as well as through the reading of books, scientific articles, jurisprudence (summarized or not) that discuss related aspects to the theme.